Modeling and Control for a Petroleum Process - Vu, Trieu Minh (Taiwan, 2010)
This paper introduces a calculation procedure for modeling and control simulation of a condensate distillation column based on the energy balance (L-V) structure. In this control, the reflux rate L and the boilup rate V are used as the inputs to control the outputs of the purity of the distillate overhead and the impurity of the bottom products. The mathematical modeling simulation is an important part for the process dynamic analysis and the plant initial design. In this paper, the mathematical modeling simulation is accomplished over three phases: the basic nonlinear model of the plant; the full-order linearised model; and the reduced-order linear model. The reduced-order linear model is then used as the reference model for a model-reference adaptive control (MRAC) system to verify the applicable ability of a conventional adaptive controller for a distillation column dealing with the disturbance and the model-plant mismatch as the influence of the plant feed disturbances.